Сравнительный анализ технологий изготовления кремниевых схем считывания информации с ИК-фотодиодов - Reva, V. Р.; Korinetz, S. V.; Pysarenko, L. A.; Dukhnin, S. E.; Barsukova, N. A. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
A comparative analysis of the advantages and disadvantages of two technologies for fabricating readout circuits for infrared photodiodes has been carried out: complementary MOS (CMOS) technology and charge-coupled device (CCD) technology based on n-channel MOS structures. Parameters of experimental samples of integrated readout circuits (IRC) with a 2×64 format, manufactured using these technologies, are presented. The results demonstrate the feasibility of producing IRCs capable of operating at cryogenic temperatures.